A retrospective on Friedman's theory of permanent income - Costas Meghir (Institute for Fiscal Studies (IFS), 2004)
Friedman's book on the Óƒonsumption FunctionÔ is one of the great works of Economics demonstrating how the interplay between theoretical ideas and data analysis could lead to major policy implications. We present a short review of Friedman's Permanent Income Hypothesis, the origins of the idea and its theoretical foundations. We give a brief overview of its influence in modern economics and discuss some relevant empirical results and the way they relate to the original approach taken by Friedman.
Keywords: B31; D11; H30; 330; Friedman; consumption function; permanent income hypothesis; Einkommenshypothese; Theorie